Italian all‐sky imager tracks auroral red arcs over Europe. (7th May 2013) - Schultz, Colin
Abstract : During geomagnetic storms, stable auroral red (SAR) arcs reach down from polar latitudes, their faint glow stretching equatorward of the traditional auroral oval. Invisible to the naked eye, SAR arcs are an upper atmospheric occurrence produced by the emission of light from oxygen atoms in the thermosphere. The excitation of the ionospheric oxygen that produces SAR arcs is caused, in turn, by the conduction of heat from the magnetospheric ring current. Advances in camera optics, including more sensitive sensors and highly specific filters, have allowed researchers to track the occurrence of SAR arcs, opening a window into the dynamics of the inner magnetosphere.